Pharmacokinetic boosting of osimertinib with cobicistat in patients with non-small cell lung cancer: The OSIBOOST trial. (September 2022) - van Veelen, Ard; Gulikers, Judith; Hendriks, Lizza E.L.; Dursun, Safiye; Ippel, Juanita; Smit, Egbert F.; Dingemans, Anne-Marie C.; van Geel, Robin; Croes, Sander
Highlights: Addition of cobicistat increased osimertinib exposure in all NSCLC patients. Addition of cobicistat to osimertinib did not lead to unexpected or severe adverse events. The osimertinib boosting effect of cobicistat was stable over time. Abstract: Introduction: Exposure to osimertinib, a third generation epidermal growth factor receptor ( EGFR ) tyrosine kinase inhibitor (TKI) for treatment of non-small cell lung cancer (NSCLC) and a sensitizing EGFR mutation, can be substantially below average. We evaluated whether plasma levels could be boosted by co-administration of cobicistat, a strong Cytochrome P450 3A-inhibitor. Methods: This was a pharmacokinetic, proof-of-concept clinical trial (the OSIBOOST trial, NCT03858491). NSCLC-patients with osimertinib were eligible if their steady state osimertinib plasma trough concentration was low (≤195 ng/mL). On day 1, the area under the plasma curve (AUC0-24, ss ) of osimertinib and its metabolite (AZ5104) was calculated using a limited sampling strategy (four samples). Cobicistat co-treatment (150 mg, once daily) was started on day 2. Between day 22–26, a second AUC was determined. Cobicistat dose could be escalated if the osimertinib trough concentration was still ≤ 195 ng/mL, in the absence of toxicity. Primary endpoint was the increase in osimertinib exposure, secondary endpoint was toxicity. Cobicistat could be continued during the expanded access phase, with follow-up (2–4 months) of the boosting effect. Results: The mean baseline osimertinib trough concentration for the eleven enrolled patients was 154 ng/mL. In all patients, cobicistat addition led to an increase in osimertinib exposure. Mean increase in total AUC0-24ss (AUC osimertinib + AUC AZ5104) was 60%, (range 19%–192%). The boosting effect was consistent over time. No grade ≥ 2 toxicity was observed. Conclusion: Pharmacokinetic boosting of osimertinib with cobicistat in patients with NSCLC is feasible without increasing toxicity, although the degree of boosting is variable.